أثر استخدام استراتيجية التعليم المتمايز القائمة على الذكاءات المتعددة على تنمية التحصيل الدراسي والاحتفاظ بالتعلم والدافعية للإنجاز لدى تلاميذ المرحلة الإبتدائية - بيومي، ياسر عبدالرحيم; الجندي، حسن عوض حسن (الجمعية المصرية لتربويات الرياضيات, 2018)
هدف البحث الحالي إلى استقصاء أثر استخدام استراتيجية التعليم المتمايز القائمة على الذكاءات المتعددة على تنمية التحصيل الدراسي والاحتفاظ بالتعلم والدافعية للإنجاز، لدى تلاميذ الصف السادس الابتدائي، وقد استخدم المنهج شبه التجريبي القائم على تصميم المجموعتين: التجريبية والضابطة ذوي القياس القبلي والبعدي، وتكونت عينة البحث من (120) تلميذا وتلميذة من تلاميذ الصف السادس الابتدائي، تم اختيارهم بطريقة مقصودة من مجتمع البحث الأصلي والمتمثل في جميع تلاميذ الصف السادس الابتدائي الذين يدرسون في المرحلة الابتدائية بمحافظة الغربية، خلال الفصل الدراسي الثاني للعام الدراسي 2017/ 2018م، وقد تكونت المجموعة التجريبية من (60) تلميذ وتلميذة درسوا وحدة "المعادلات والمتباينات" من كتاب الرياضيات للصف السادس الابتدائي باستخدام استراتيجية التعليم المتمايز القائمة على الذكاءات المتعددة، كما تكونت المجموعة الضابطة من (60) تلميذ وتلميذة درسوا نفس المحتوى بالاستراتيجية المعتادة، وتم تطبيق أدوات البحث والمتمثلة في: الاختبار التحصيلي ومقياس الدافعية للإنجاز على مجموعتي البحث، وقد أسفرت النتائج عن وجود فرق دال إحصائيا عند مستوى (α ≤ 0.05) بين متوسطي درجات تلاميذ المجموعتين التجريبية والضابطة في التطبيق البعدي لكل من: الاختبار التحصيلي ومقياس الدافعية للإنجاز لصالح المجموعة التجريبية وبحجم تأثير مرتفع، كما أسفرت النتائج عن عدم وجود فرق دال إحصائيا عند مستوى (α ≤ 0.05) بين متوسطي درجات تلاميذ المجموعة التجريبية في التطبيقين البعدي والبعدي المؤجل؛ مما يدل على الاحتفاظ بالتعلم لدى تلاميذ المجموعة التجريبية للوحدة المختارة، كما أشارت النتائج أيضا إلى وجود علاقة ارتباطية موجبة دالة إحصائيا عند مستوى (α ≤ 0.05) بين درجات تلاميذ المجموعة التجريبية في التطبيق البعدي للاختبار التحصيلي ومقياس الدافعية للإنجاز. وفي ضوء النتائج أوصى البحث الحالي بضرورة تطبيق واستخدام استراتيجية التعليم المتمايز القائمة على الذكاءات المتعددة في تعليم وتعلم الرياضيات بالمرحلة الابتدائية، وضرورة الاهتمام بالتدريب على تنمية الدافعية للإنجاز لدى المتعلمين بمختلف المراحل الدراسية من خلال تدريس الرياضيات، وقد قدم البحث الحالي مجموعة من الدراسات والبحوث المقترحة في هذا الصدد.
The present study investigates the effect of using a differentiated instruction strategy based on multi-intelligences on developing academic achievement, prolonged impact of learning, and achievement motivation of primary sixth grade students. The study used a quasi-experimental design with two groups: experimental and control and two assessments: pre and post. The purposely selected sample of the study comprised (120) sixth graders: males and females representing sixth graders studying at El-Gharbia governorate during the second term of the academic year 2017/2018. The experimental group comprised 60 students: males and females who studied (the Equations and Differences) unit of the sixth grade mathematics book using the proposed A differentiated instruction strategy based on multi-intelligences strategy. The control group of the study comprised (60) students: males and females who studied the same content based using traditional learning strategies. The tools of the study: Achievement test and achievement motivation scales have been administered to both groups participating in the study. The results of the study indicated there were statistically significant differences at the (α ≤ 0.05) level between the mean scores of the experimental and control groups in favor of the experimental group on the post administration of both the achievement test and achievement motivation Scale. The results also indicated there were no statistically significant differences at the (α ≤ 0.05) level between the mean scores of the experimental group on the post and the delayed post administration of both the achievement test and achievement motivation Scale indicating the prolongation of the learning effect among the group on the selected unit. The result also indicated there was statistically significant positive correlation at the (α ≤ 0.05) level between the mean scores of the experimental group on the post administration of the achievement test and achievement motivation Scale. Based on these results, the present study recommends adopting the A differentiated instruction strategy based on multi-intelligences in teaching and learning mathematics in the primary stage of education. The study also recommends paying a great attention to the importance of training on developing and promoting achievement motivation among learners across the various stages of mathematics education. The present study proposes a number of related studies of interest.
Keywords: التعليم المتمايز -- الذكاءات المتعددة -- التحصيل الدراسى -- دافعية الإنجاز -- المرحلة الابتدائية